Pulmonary embolism and deep vein thrombosis caused by nitrous oxide abuse: A case report - Sun, Wen (World J Clin Cases, 2019)
BACKGROUND: Nitrous oxide (N(2)O) has gained increasing popularity as a recreational drug, causing hallucinations, excitation, and psychological dependence. However, side effects have been reported in recent years. Our case report proposes a correlation among N(2)O, pulmonary embolism (PE), and deep vein thrombosis (DVT) and emphasizes the role of homocysteine (Hcy) in thrombotic events. CASE SUMMARY: A 29-year-old man with long-term N(2)O abuse sought evaluation after acute chest pain. A diagnostic workup revealed PE, DVT, and hyperhomocysteinemia. The patient was successfully treated with thrombolytic and anticoagulant therapy. Moreover, his Hcy level decreased and returned to normal after Hcy-lowering therapy. CONCLUSION: Chronic N(2)O abuse might increase the risk of PE and DVT, although there have been few studies previously.